2013
DOI: 10.30955/gnj.000694
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between airborne microbial and particulate matter concentrations in the ambient air at a mediterranean site

Abstract: The relationship between the viable airborne bacterial and fungal concentrations and the respirable particulate matter with aerodynamic diameter less than 10 μm (PM10), 2.5 μm (PM2.5), and 1 μm (PM1) in the ambient air was studied. An Andersen six stage viable particle sampler and a MAS 100 sampler were used for microbial measurements. Duplicates of samples were collected at each sampling period (20 campaigns in total) at a residential site in the city of Chania (Crete, Greece) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…did not appear to be influenced by wind conditions, as the results of the bioaerosol measurements showed in a Greek city [57]. Other authors reported that there are definitely positive correlations between mesophilic bacterial concentrations and wind speeds of 1-3 m/s [55,56,70]. Perez (2012) observed a positive correlation (rho = 0.34) between fine and coarse particles during days with and without Saharan dust [71].…”
Section: Environmental Influencing Factorsmentioning
confidence: 74%
See 2 more Smart Citations
“…did not appear to be influenced by wind conditions, as the results of the bioaerosol measurements showed in a Greek city [57]. Other authors reported that there are definitely positive correlations between mesophilic bacterial concentrations and wind speeds of 1-3 m/s [55,56,70]. Perez (2012) observed a positive correlation (rho = 0.34) between fine and coarse particles during days with and without Saharan dust [71].…”
Section: Environmental Influencing Factorsmentioning
confidence: 74%
“…In this study, a negative correlation could be found between mesophilic bacterial concentrations and air humidity in the three geographical regions. Other investigations concluded that there are no correlations between mesophilic bacterial concentrations and air humidity [55][56][57][58]. Yao et al (2010) noted that the relatively large size of airborne particles allows for absorbance of more moisture from the air when the humidity increases.…”
Section: Environmental Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation